Artificial Intelligence in Developing Countries: A Systematic Review of Cross-Sector Applications, Implementation Challenges in South Asian countries. - Md. Farhan Hossan Tamin; Morium Akter Shefa; Md. Ruhul Amin; Md. Salim Md. Salim (Social Science Research Journal, 2026)
In South Asia countries like Bangladesh, India, Pakistan, Sri Lanka and Nepal, artificial intelligence (AI) is rapidly changing several sectors. AI has aided solar energy forecasting, disaster prediction, healthcare diagnostics, agriculture precision, HRM, financial compliance in Bangladesh. This discourse identifies various applications of AI/ML in the field of environmental studies, healthcare, education, agriculture, and smart energy systems, with a focus on the Indian context, aiming to augment predictive accuracy and personalization. AI is used in Pakistan, especially in, personalized e-learning, covid-19 detection and prediction, breeding plants, and data-driven business decisions by advanced deep learning models. AI for Good: Sri Lanka showcases Health Misinformation Detection and Digital Drones, Technology for the Public Sector, Chatbots for Education, and presents a strong position on governance and ethical issues Nepal — Nepal is also showing the early signs of AI adoption in healthcare, education, and fintech space. However, amid critical opportunities to boost productivity and decision-making, poor data quality, inadequate infrastructure, ethical considerations, skill gaps, and rural access problems call for tailor-fitting policies, as well as capacity bolstering.